Educational Reform and the Teaching Profession - Purvaneckienė, Giedrė (Acta Paedagogica Vilnensia, 1996)
In 1992 the laboratory of Sociology of Vilnius University conducted a survey, in which 623 teachers from various regions of Lithuania, as well as 355 students of education of several Lithuanian universities completed a questionnaire. The main results of the survey are presented in the article. The research showed teachers attitude towards the ongoing educational reform as well as the motivation for choosing the profession of educator. Opinions on personal traits of the teachers were expressed during the research, as well as the outlooks on the existing system of teacher training. Questions clarifying teachers’ opinions about their job were also included in the questionnaire. The results show opinions of the educators about the teaching profession does not differ greatly from general opinion of the Lithuanian population, but, on the other hand, most of the present and the would-be teachers consider their professional training as insufficient.
Keywords: Educational reform; teacher; personal traits of the teachers; teacher training.